An analysis of the generic structure of acknowledgements written by postgraduate students in the Faculty of Education, Universiti Teknologi Mara (UiTM) / Nazarul Azali Razali - Razali, Nazarul Azali (2011)
In the field of genre studies, the acknowledgement is probably the least studied section of the research article or research report. The three main specific objectives of this study are (a) to identify the structure of acknowledgements written by postgraduate students at the Faculty of Education UiTM, (b) to identify the obligatory and optional moves that help to realize the structure of those acknowledgements, and (c) to examine gender differences in the display of gratitude in those acknowledgements. A contextual analysis that involves qualitative and quantitative approaches were used for the study that involved collection and analysis of a corpus of masters dissertation acknowledgements (MDAs) written by Malay and Bumiputera postgraduate students at the Faculty of Education, Universiti Teknologi MARA. The following models were adopted as analysis models: Al-Ali's (2006:37) modified Generic Structure of English Dissertation Acknowledgements written by non-native Arab writers which was modified from Hyland's (2004:308) Generic Structure of Dissertation Acknowledgements; and Mingwei & Yajun's (2010:103-104) analysis of linguistic features in masters and PhD acknowledgements which was adopted from Hyland & Tse (2004). The findings of the study revealed that the acknowledgement structure of MDAs at the Faculty of Education UiTM has the same structure as the model by Al-Ali (2006). While maintaining the model by Al-Ali (2006), a modified generic structure of MDAs that is representative of the discourse community of postgraduate students at the Faculty of Education, UiTM is proposed. In the case of gender differences, the results of the study indicated that there are differences across gender in terms of the presence of the moves/steps in the structure of acknowledgement and linguistics patterns in the thanking acts and authorial choice. The results of this study proves that the acknowledgement is in itself a genre with a specific communicative purpose written based on the accepted norms of the society and the academic culture of a particular discourse community; and that it is vital that students are to be made aware of the writing conventions of this genre especially non-native speakers of the language as to aid their understanding of the writing processes and the workings of academic writing. This study recommends that future works should be done with a larger national corpus with special investigations into the patterns and variations of generic structure, linguistic features and grammatical structures across academic levels, race and ethnicities, as well as gender.